Associations Between Maternal Distress, Cortisol Levels, and Perinatal Outcomes. Issue 3 (24th April 2022) - Lundholm, Cecilia; Rejnö, Gustaf; Brew, Bronwyn; Smew, Awad I.; Saltvedt, Sissel; Almqvist, Catarina
ABSTRACT: Objective: Stress during pregnancy may decrease gestational age at birth and birth size. We aimed to investigate the associations between maternal subjective stress measures, salivary cortisol, and perinatal outcomes. Methods: A cohort of pregnant women ( n = 1693) was recruited from eight antenatal care clinics in Stockholm, Sweden. Questionnaires on subjective distress (perceived stress, worry, depression symptoms, sleep quality) and saliva samples for cortisol measurement (morning and evening) were collected in early and late pregnancy. Perinatal outcomes were birth weight, birth length, gestational age, and birth weight for gestational age. We used linear regression to estimate associations adjusted for maternal characteristics. Results: All associations between subjective distress and cortisol levels were close to null and nonsignificant, for example, exp( β ) = 1.001 (95% confidence interval = 0.995 to 1.006) for the morning cortisol level and perceived stress in early pregnancy. Likewise, most associations between distress (subjective and cortisol) and perinatal outcomes were weak and not statistically significant, for example, β = 1.95 (95% confidence interval = −4.16 to 8.06) for perceived stress in early pregnancy and birth weight. An exception was a statistically significant association between birth weight for gestational age and depression symptoms in early pregnancy, with somewhat higher weight with more symptoms ( β = 0.08; 95% CI = 0.04 to 0.13). The results were similar for stress in early and late pregnancy. Conclusions: We found no association between subjective distress and cortisol measures irrespective of when in pregnancy the measures were taken. Furthermore, we found no evidence for a longitudinal association between psychological measures of stress or cortisol with lower birth weight, birth weight for gestational age, or gestational age.